Lydia Cabrera and the construction of an Afro-Cuban cultural identity - Rodríguez-Mangual, Edna M. (Envisioning Cuba., 2004)
Lydia Cabrera (1900-1991) collected oral histories, stories, and music from Cubans of African descent. Her work is often viewed as an extension of the work of her famous brother-in-law, Cuban anthropologist Fernando Ortiz. Edna Rodriguez-Mangual challenges this, proposing that her work is an alternative to the hegemonizing national myth of Cuba.